2020
DOI: 10.1088/1757-899x/944/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of urban and rural environmental quality: the opinions of residents of the region

Abstract: The article presents the results of a comparative analysis of the opinions of the rural and urban settlements’ population of the Stavropol Territory on the qualitative characteristics of the living environment. The quality of life in the village, which to a small extent depends on the state of the environment (transport accessibility of infrastructure and social facilities, road and pavement, lighting, etc.), plays a significant role in the choice of permanent residence. Currently, the rural population has hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Zhou et al found that infrastructure, public service facilities, and the natural ecological environment were the main aspects of change when analyzing the element characteristics of the quality of rural human settlements in the suburbs of Beijing; further, they found that the supporting infrastructure and social coordination level were the most important for villagers to form an overall impression of a village [7]. Baklanov et al proposed that infrastructure and social facilities represent the quality characteristics of the living environment to a certain extent, adding that the unique spatial organization of rural settlements and villagers' lifestyles are also very important [8]. Yu et al divided the built environment elements into three categories: fixed elements, such as public infrastructure and buildings; semi-fixed elements, such as landscapes and signs; and non-fixed elements, such as representative people and their behaviors [9].…”
Section: Research On the Elements Of Architectural Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al found that infrastructure, public service facilities, and the natural ecological environment were the main aspects of change when analyzing the element characteristics of the quality of rural human settlements in the suburbs of Beijing; further, they found that the supporting infrastructure and social coordination level were the most important for villagers to form an overall impression of a village [7]. Baklanov et al proposed that infrastructure and social facilities represent the quality characteristics of the living environment to a certain extent, adding that the unique spatial organization of rural settlements and villagers' lifestyles are also very important [8]. Yu et al divided the built environment elements into three categories: fixed elements, such as public infrastructure and buildings; semi-fixed elements, such as landscapes and signs; and non-fixed elements, such as representative people and their behaviors [9].…”
Section: Research On the Elements Of Architectural Featuresmentioning
confidence: 99%
“…Among these levels, changes in construction land at the village level have been found to largely reflect changes in the number and size of buildings, which had a greater degree of influence on a village's architectural features than other changes. Furthermore, at the street level, public facilities and spaces, as important comprehensive places for villagers' daily lives and social communication, have been found to be the main carriers of a village's social features [7,8]. Studying these places is of great significance for understanding changes in village architectural features at the street level.…”
Section: Summary Of Previous Studies and The Framework Of This Studymentioning
confidence: 99%